Exploring the Pharmaceutical Consumer Journey: Evidence from Community Pharmacies in Londrina, Brazil - Suaiden, André Schmidt; Cardoso, Bruce Soares; Oliveira, Robson da Silva de; Araujo, Dayse Maciel de (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
Pharmaceutical retail in Brazil has undergone a structural transformation, integrating clinical services alongside the sale of medicines and beauty products. This study investigates the pharmaceutical consumer journey in community pharmacies in Londrina (Paraná), focusing on the impact of clinical services (such as consultations and laboratory tests) on consumer decision-making and store loyalty. A quantitative survey was administered to 118 residents of the city, collecting data on purchasing behavior, service awareness, and perceptions of pharmacists' roles. Results show that women are the primary decision-makers in pharmaceutical purchases, often combining health and cosmetic product needs. Consumers value convenience, product organization, and customer service, but awareness of clinical services remains limited. The study contributes to the marketing literature by detailing a consumer journey that blends traditional retail dynamics with emerging health service expectations. The findings offer insights into the optimization of store layout, communication strategies, and service design for pharmaceutical retailers aiming to enhance customer experience and loyalty.